1989
DOI: 10.1111/j.1479-828x.1989.tb01773.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Appendicitis in Pregnancy

Abstract: Acute appendicitis is the commonest nongynaecological surgical problem occurring during pregnancy. Almost 10 year's experience at a large teaching hospital is supplemented with an extensive review of the literature to offer guidelines for diagnosis and management. Symptoms, signs and investigations are unhelpful in diagnosis. The overwhelming message is that because perinatal mortality rises from less than 3% in both uncomplicated appendicitis and negative laparotomy, to 20% in perforated disease, the maxim re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 17 publications
3
13
0
1
Order By: Relevance
“…McGee et al reported a negative appendectomy rate as low as 3% [2]. McGory and colleagues reported a rate of 23%, which is one of the most widely reported studies in the literature [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McGee et al reported a negative appendectomy rate as low as 3% [2]. McGory and colleagues reported a rate of 23%, which is one of the most widely reported studies in the literature [12].…”
Section: Discussionmentioning
confidence: 99%
“…Among all surgeries during pregnancy, 25% are performed due to non-obstetrical indications [1][2][3]. Th e incidence of acute appendicitis is the same in pregnant and non-pregnant women.…”
Section: Introductionmentioning
confidence: 96%
“…[21,22] Terzi et al found rate of 13% [14] and Miloudi et al reported negative appendectomy rate of 3.4%. [23] Present study finding of 30% rate is higher than literature findings, but may be explained by inability to perform MRI or presence of physical findings that indicated urgent exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal morbidity from appendicitis is very uncommon; however, there is a significant risk to the pregnancy with reported fetal loss rates of 2-4% related to nonperforated appendicitis and 3-10% related to negative appendectomy. The fetal loss rate increases dramatically to 24% in the setting of perforated appendicitis [16][17][18]. In addition, the risk for preterm delivery is increased after appendectomy, particularly during the first postoperative week [5,17,19].…”
Section: Introductionmentioning
confidence: 99%